2022
DOI: 10.1167/jov.22.6.1
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and serial choice bias for low-level visual features are unaltered in autistic adolescents

Abstract: Autism spectrum disorder (ASD), or autism, is characterized by social and non-social symptoms, including sensory hyper- and hyposensitivities. A suggestion has been put forward that some of these symptoms could be explained by differences in how sensory information is integrated with its context, including a lower tendency to leverage the past in the processing of new perceptual input. At least two history-dependent effects of opposite directions have been described in the visual perception literature: a repul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
(92 reference statements)
1
3
0
Order By: Relevance
“…For instance, fMRI experiments have found preserved repetition suppression for geometric shapes (Ewbank et al, 2017) and objects (Utzerath et al, 2018) and behavioral experiments have found no differences in adaptation for simple stimulus features, such as color (Maule et al, 2018) and line orientation (Bosch et al, 2022), and using non-social stimuli (Karaminis et al, 2015). Together, these studies support our conclusion that the influence of temporal context may be preserved in autism, at least for non-social stimuli.…”
Section: Discussionsupporting
confidence: 80%
“…For instance, fMRI experiments have found preserved repetition suppression for geometric shapes (Ewbank et al, 2017) and objects (Utzerath et al, 2018) and behavioral experiments have found no differences in adaptation for simple stimulus features, such as color (Maule et al, 2018) and line orientation (Bosch et al, 2022), and using non-social stimuli (Karaminis et al, 2015). Together, these studies support our conclusion that the influence of temporal context may be preserved in autism, at least for non-social stimuli.…”
Section: Discussionsupporting
confidence: 80%
“…The half violin plot indicates the median (white circle), interquartile ranges (black rectangles) and the density distribution (blue shape). Studies ranked along the abscissa are 1 ( Bae & Luck, 2019 ) 2 ( Bae & Luck, 2017 ) 3 ( Ceylan et al, 2021 ) 4 ( Bosch et al, 2022 ) 5 ( Murai & Whitney, 2021 ) 6 ( Fritsche et al, 2020 ) 7 ( Pascucci et al, 2019 ) 8 ( Fischer & Whitney, 2014 ) 9 ( Myers et al, 2018 ) 10 ( Gallagher & Benton, 2022 ) 11 ( Collins, 2019 ) 12 ( Galluzzi et al, 2022 ) 13 ( Cicchini et al, 2021 ) 14 ( van Bergen & Jehee, 2019 ) 15 ( Teng et al, 2022 ) 16 ( Wildegger et al, 2015 ) 17 ( Cicchini et al, 2018 ) 18 ( Kondo et al, 2022 ) 19 ( Samaha et al, 2019 ) 20 (M. Luo et al, 2022 ) 21 ( Abreo et al, 2023 ) 22 ( Fritsche et al, 2017 ) 23 ( Lau & Maus, 2019 ) 24 ( Rafiei et al, 2021b ) 25 ( Ceylan et al, 2021 ) 26 ( Gekas et al, 2019 ) 27 ( Cicchini et al, 2017 ) 28 ( Manassi et al, 2017 ) 29 ( Zhang & Alais, 2020 ) 30 ( Liberman et al, 2016 ) 31 ( Rafiei et al, 2021a ) 32 ( Mikellidou et al, 2021 ) 33 ( John-Saaltink et al, 2016 ) 34 ( Sheehan & Serences, 2022 ) 35 ( Kim et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…A more nuanced understanding of choice history bias adaptation may be crucial to pinpointing the source(s) of individual differences. Despite the recent popularity of theories postulating an imbalance in the integration of prior and sensory information (e.g., Brock, 2012 ; Pellicano & Burr, 2012 ; Sinha et al, 2014 ), there is mixed evidence on choice history biases being atypical in ASD, with previous studies reporting decreased ( Lieder et al, 2019 ), increased ( Feigin, Shalom-Sperber, Zachor, & Zaidel, 2021 ) and unaltered choice history biases ( Bosch, Fritsche, Utzerath, Buitelaar, & de Lange, 2022 ). Because a broader literature has suggested that altered perceptual processing may be due to atypical learning of the environment statistics ( Karvelis et al, 2018 ; Lawson et al, 2014 ; Noel, Zhang, Stocker, & Angelaki, 2021 ), here we had hypothesized that the reliance on choice history might be particularly affected when adapting to a new sequential structure.…”
Section: Discussionmentioning
confidence: 99%